Creating XML schemas for lexicographical projects - Ledinek, Nina (Slovenski jezik, 2013)
The article discusses the strategies applied for creating XML Schemas in dictionary projects, based on experience gained during creation of the schema of the Dictionary of the Slovene Literary Language of the 16th Century, and itexplains how the different possibilities of the construction of XML Schemas influence the lexicographical work and the subsequent use of the dictionary. Three general aspects to be considered in designing schemas for dictionary projects are described in the article: the content aspect, the practical aspect, and the technical aspect. On this basis, the decision on the formal description method of the structure in a given schema definition language is made and justified
Keywords: dictionary databases; Dictionary of the Slovene literary language of the 16th century; Fran Ramovš Institute of the Slovene language; Inštitut za slovenski jezik Frana Ramovša ZRC SAZU; leksikografija; lexicography; podatkovne baze; Slovar slovenskega knjižnega jezika 16. stoletja; Slovene; Slovene language; slovenščina; XML schemas; XML-sheme